2014
DOI: 10.1016/j.freeradbiomed.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Nrf2 Induction by Protein Transduction Attenuates Osteoclastogenesis

Abstract: It has been reported that reactive oxygen species (ROS) play a role as intracellular signaling molecules in RANKL stimulation. Previously we demonstrated that induction of cytoprotective enzyme expression by Nrf2-gene transfer successfully ameliorated RANKL-dependent osteoclastogenesis. In the present study, we hypothesized that Nrf2 activation by inhibiting ubiquitination and degradation of Nrf2 by ETGE-peptide would induce Nrf2-dependent cytoprotective enzyme expression, attenuate ROS signaling, and thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…To further confirm the effects of SFC and ALA on cell proliferation, RAW264.7 cells were plated on 24‐well plates and were cultured with various concentrations of SFC and ALA for 1 d. Whole‐cell protein lysate was prepared by using lysis buffer (18), and protein concentration was measured and calculated as protein content per well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the effects of SFC and ALA on cell proliferation, RAW264.7 cells were plated on 24‐well plates and were cultured with various concentrations of SFC and ALA for 1 d. Whole‐cell protein lysate was prepared by using lysis buffer (18), and protein concentration was measured and calculated as protein content per well.…”
Section: Methodsmentioning
confidence: 99%
“…Primary Abs for Nrf2, HO1, NQO1, histone H3, and β‐actin are described in Kanzaki et al . (18). Anti‐BACH1 Ab was purchased from Abnova (Taipei, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, RANKL stimulation decreases expression of NRF2-dependent cytoprotective enzymes, thereby facilitating intracellular ROS signaling (Kanzaki et al, 2013, 2016b). Induction of cytoprotective enzymes by NRF2 activation subsequently inhibits osteoclastogenesis (Kanzaki et al, 2013, 2014, 2015; Sakai et al, 2013; Gambari et al, 2014; Lee et al, 2014; Lu et al, 2015; Bhattarai et al, 2016). Inversely, augmented osteoclastogenesis and bone destruction was observed with NRF2 deficiency (Rana et al, 2012; Hyeon et al, 2013; Ibanez et al, 2014; Lippross et al, 2014; Sun et al, 2015).…”
Section: Mechanisms That Protect Against Oxidative Stressmentioning
confidence: 99%
“…One protective mechanism involves nuclear factor E2-related factor 2 (NRF2), a master regulatory transcription factor for the synthesis of cytoprotective enzymes. NRF2 has been reported to be a negative regulator of osteoclastogenesis (Kanzaki et al, 2013, 2014, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…9 Excessive oxidative stress seems to play an important role in the destruction of periodontal tissues. 13 Previous studies have indicated that NFE2L2/NRF2 activation suppresses osteoclastogenesis, 14 it protects periodontal ligament stem cells from oxidative stress-related apoptosis, 15 and its down-regulation in oral neutrophils is associated with chronic periodontitis in humans. 12 The cytoprotective role of KEAP1 and NFE2L2/NRF2 in the reduction of inflammatory signaling and oxidative damage is highly important and has been reviewed recently.…”
mentioning
confidence: 99%